2022
DOI: 10.1017/s0003055422000430
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pregnancy on Engagement with Politics. Toward a Model of the Political Consequences of the Earliest Stages of Parenthood

Abstract: How do pregnancy and childbirth affect engagement in politics and society? Our data from a large-scale citizen panel record political engagement before, during, and after pregnancy for (future) mothers and fathers. We find that women demobilize from politics and societal issues during pregnancy. This disengagement is strongest for indicators of political participation and seeking of political news. Our analysis also shows that gender gaps in political engagement are not only strengthened but also partly create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previous studies during the transition to parenthood found that parents report a lower frequency of physical activity and engagement in politics (Abbasi & van den Akker, 2015;Naurin et al, 2022;Sjögren Forss & Stjernberg, 2019). Beyond a general decrease in leisure activities, there may also be gender differences during this transition.…”
Section: Leisure Activities and Couple Dynamicsmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies during the transition to parenthood found that parents report a lower frequency of physical activity and engagement in politics (Abbasi & van den Akker, 2015;Naurin et al, 2022;Sjögren Forss & Stjernberg, 2019). Beyond a general decrease in leisure activities, there may also be gender differences during this transition.…”
Section: Leisure Activities and Couple Dynamicsmentioning
confidence: 88%
“…In addition, we found that fathers were also more likely to listen to the news on the radio, podcasts, or TV. Male partners of pregnant women maintain engagement in politics and societal issues during a pregnancy more so than pregnant women (Naurin et al, 2022), so expectant fathers may be more prone to interact with the news.…”
Section: How Does Frequency Of Six Leisure Activities Differ Between ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to heterosexist discrimination may alter the marriage dynamics (Egan 2012; Proctor 2022) while specific socio-political factors can also be behind these results (Lewis, Rogers, and Sherrill 2011; Swank 2019; Turnbull-Dugarte, and McMillan 2023). Also, being pregnant and having children can lessen political participation (Naurin, Stolle, and Markstedt 2023). The effect of pregnancy on engagement with politics toward a model of the political consequences of the earliest stages of parenthood (Naurin, Stolle, and Markstedt 2023) and same-sex couples have less children than heterosexual couples.…”
Section: Discussionmentioning
confidence: 99%
“…Also, being pregnant and having children can lessen political participation (Naurin, Stolle, and Markstedt 2023). The effect of pregnancy on engagement with politics toward a model of the political consequences of the earliest stages of parenthood (Naurin, Stolle, and Markstedt 2023) and same-sex couples have less children than heterosexual couples. The data was collected during the height of LGBT activism around marriage rights, and the level of activism among same-sex married couples might lessen when LGB marriages become more normalized throughout society.…”
Section: Discussionmentioning
confidence: 99%